Composition of mineral elements and bioactive compounds in tartary buckwheat and wheat sprouts as affected by natural mineral-rich water. (May 2016) - Pongrac, Paula; Potisek, Mateja; Fraś, Anna; Likar, Matevž; Budič, Bojan; Myszka, Kinga; Boros, Danuta; Nečemer, Marijan; Kelemen, Mitja; Vavpetič, Primož; Pelicon, Primož; Vogel-Mikuš, Katarina; et al.
Abstract: The aim was to determine how the nutritional composition of Tartary buckwheat ( Fagopyrum tataricum Gaertn.) and wheat ( Triticum aestivum L.) sprouts is affected by the mineral composition of different waters used during their cultivation. We used tap water (TW) and two mineral-rich waters (MRWs), namely moderately mineral-rich water (MMRW) and extremely mineral-rich water (EMRW) originating from springs that contain naturally present mineral elements. Grain germination was not negatively affected by MRWs, however EMRW impeded radicle growth, and consequently prevented sprout development. In comparison to cultivation in TW, cultivation in MMRW resulted in higher Na, Mg, K and Mn concentrations in both sprouts. There were no water-related effects on distribution of mineral elements within plant species, however there were differences in Ca distribution. In Tartary buckwheat Ca was located in inter-vasculature mesophyll, presumably as oxalate crystals. In wheat Ca predominated in epidermis. Only in Tartary buckwheat cultivation in MMRW resulted in less dietary fibre and catechin and more quercetin. By capturing compositional profiles of mineral elements and bioactive compounds in Tartary buckwheat and wheat sprouts we identified the potential for selective enhancement of MMRW. We suggest further work using different spring MRWs to identify optimal conditions for cultivation of different sprouts. Highlights: Successful sprout development depended on the mineral element (ME) composition of waters. ME concentration but not distribution was affected by ME composition of water. Total dietary fibre was affected by ME composition of waters only in Tartary buckwheat sprouts. Quercetin and catechin, but not rutin concentration depended on ME composition of waters.